Cobalt-nickel / attapulgite-based mordenite catalyst as well as preparation method and application thereof
By using the cobalt-nickel/concave-concave-based mordenite catalyst, the problems of low active hydrogen adsorption capacity and insufficient selectivity of target product yield in the depolymerization of lignin are solved, and lignin is efficiently depolymerized under low conditions and high yield guaiocyanol is produced.
Patent Information
- Application Number
- CN202411792080.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing cobalt-based catalysts have low adsorption capacity for active hydrogen in lignin depolymerization, require high temperature and pressure, and have low yield and selectivity of the target product, making it difficult to effectively depolymerize lignin.
The mordenite support is prepared by hydrothermal method using a cobalt-nickel/concave-concave-copper mordenite catalyst, and the cobalt and nickel active components are supported thereon, optimizing the structure and composition of the catalyst to improve its activity and selectivity.
Under lower temperature and pressure conditions, a lignin conversion rate of 100%, guaiocorol yield is greater than 30%, and guaiocorol product yield is greater than 80%, which improves the economic benefits and product concentration of the catalyst.
Smart Images

Figure CN119588405A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lignin depolymerization, and in particular to a cobalt-nickel / attapulgite-based mordenite catalyst and a preparation method and application thereof. Background Art
[0002] Biomass is the main sustainable source of organic carbon in nature, providing great potential for addressing environmental challenges and promoting a carbon-neutral society. Lignin is an important component of lignocellulosic biomass, so it is imperative to rationally develop and utilize lignin. In recent years, converting lignin into value-added products such as bio-oil and phenolic compounds through thermochemical methods such as liquefaction and pyrolysis has become a promising technology.
[0003] It is reported that cobalt-based catalysts can achieve the selective breaking of ether bonds in lignin. At the same time, due to their low price and stable performance, they are often used for lignin depolymerization. However, cobalt-based catalysts have low adsorption energy for active hydrogen, and usually require higher temperatures and pressures (temperature greater than 350°C, pressure greater than 10MPa during the reaction). In addition, the macromolecular fragments produced by lignin cracking are highly reactive and easily repolymerized into polymers, resulting in a lower expected yield or selectivity of the target product. Therefore, improving the intrinsic activity and selectivity of cobalt-based catalysts is a challenge for current research. Summary of the invention
[0004] The main purpose of the present invention is to provide a cobalt-nickel / attapulgite-based mordenite catalyst capable of catalyzing the depolymerization of lignin to prepare guaiacol, which has low reaction condition requirements and high target product selectivity, and a preparation method and application thereof.
[0005] To achieve the above-mentioned purpose, the present invention provides a cobalt-nickel / attapulgite-based mordenite catalyst, comprising a carrier and an active component loaded on the carrier, wherein the carrier is attapulgite-based mordenite, the active components are cobalt and nickel, and the attapulgite-based mordenite is prepared by a hydrothermal method using attapulgite as a raw material to obtain mordenite.
[0006] Furthermore, the content of nickel is 5-15 wt%, the content of cobalt is 5-15 wt%, and the balance is attapulgite-based mordenite.
[0007] The present invention also provides a method for preparing the above-mentioned cobalt-nickel / attapulgite-based mordenite catalyst, comprising the following steps:
[0008] (1) mixing the acid-treated attapulgite with tetraethylammonium bromide, sodium hydroxide, sodium aluminate and water, and then subjecting the mixture to hydrothermal crystallization. The obtained product is sequentially washed, dried and calcined to obtain sodium-type attapulgite-based mordenite;
[0009] (2) adding sodium-type attapulgite-based mordenite into a sodium chloride aqueous solution for ion exchange treatment to obtain attapulgite-based mordenite;
[0010] (3) Cobalt and nickel are loaded on attapulgite-based mordenite to obtain the cobalt-nickel / attapulgite-based mordenite catalyst.
[0011] Furthermore, in step (1), the mass ratio of the acid-treated attapulgite to tetraethylammonium bromide, sodium hydroxide, sodium aluminate and water is 1:0.08:0.42:0.1-0.5:40, and the temperature of the hydrothermal crystallization treatment is 160-220°C, and the time is 92-200h.
[0012] Furthermore, in step (1), the drying temperature is 50-80°C for 12-24 hours; the calcination is carried out in an air atmosphere, and the specific process is to heat the temperature to 450-600°C at a heating rate of 1-5°C / min and calcine for 4-10 hours.
[0013] Furthermore, in step (2), the concentration of the sodium chloride aqueous solution is 1-5 mol / L, the temperature of the ion exchange treatment is 90° C., the time is 4 h, and the number of ion exchange treatments is three times.
[0014] Furthermore, the specific process of step (3) is: adding the attapulgite-based mordenite to the cobalt precursor salt solution, stirring at room temperature for 12 to 24 hours, then evaporating the solvent, and then drying at 50 to 80° C. for 12 to 24 hours, and finally calcining at 450 to 600° C. in an air atmosphere at a heating rate of 1 to 5° C. / min for 4 to 10 hours to obtain cobalt / attapulgite-based mordenite;
[0015] The cobalt / attapulgite-based mordenite is added to a nickel precursor salt solution, stirred at room temperature for 12 to 24 hours, and then the solvent is evaporated, and then dried at 50 to 80° C. for 12 to 24 hours, and finally calcined at 450 to 600° C. in an air atmosphere at a heating rate of 1 to 5° C. / min for 4 to 10 hours to obtain the cobalt-nickel / attapulgite-based mordenite catalyst.
[0016] The present invention also provides the use of the above catalyst in catalyzing the depolymerization of lignin to prepare guaiacol under the condition of using water, glycerol and formic acid as reaction solvents and without an external hydrogen source.
[0017] The present invention also provides a method for preparing guaiacol by catalyzing the depolymerization of lignin, comprising the following steps: mixing glycerol, deionized water and formic acid in a volume ratio of 1:1 to 10:0.1 to obtain a reaction solvent, and adding the reaction solvent, lignin and the catalyst as claimed in claim 1 or 2 into a reactor for reaction.
[0018] Furthermore, the volume mass ratio of the reaction solvent, lignin and catalyst is 11.1-55.5 ml: 1 g: 0.1-0.5 g, and the reaction conditions are temperature 270-350° C., stirring rate 400-800 r / min, and reaction time 6-12 h.
[0019] The catalyst of the present invention uses attapulgite-based mordenite as a carrier. The pore size of the mordenite synthesized using attapulgite as a raw material is optimized, and the generated mesoporous structure is conducive to the depolymerization of lignin. At the same time, the eight-membered ring and twelve-membered ring structure in the mordenite provide abundant B acid sites, which play a key role in the adsorption and activation of CC bonds and CO bonds in lignin.
[0020] The cobalt and nickel mixture as active components can enhance the catalyst's ability to activate hydrogen in the hydrogen-donating solvent into active hydrogen ions; the cobalt is dispersed with the addition of metallic nickel, making it more evenly dispersed on the carrier, which is attributed to the interaction between the metals. The cobalt and the aluminum in the carrier undergo structural changes to form Co-O-Al bonds. At the same time, the metal interaction between nickel and cobalt leads to the generation of oxygen defects, and the presence of oxygen defects can enhance the adsorption polarization of the catalyst on the ether bonds in lignin, thereby promoting the depolymerization of lignin.
[0021] The beneficial effects of the present invention are embodied in:
[0022] The catalyst of the invention is used for catalytic depolymerization of lignin to prepare guaiacol. In a water, glycerol and formic acid system and a nitrogen atmosphere, a 100% lignin conversion rate can be achieved, a guaiacol yield of more than 30%, and a guaiacol product yield of more than 80%. The catalyst has the advantages of high economic benefit and concentrated products, can improve the depolymerization ability and selectivity of the catalyst for lignin, and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the XRD spectrum of the attapulgite-based mordenite prepared in Example 1.
[0024] Figure 2 This is a SEM image of the attapulgite-based mordenite prepared in Example 1.
[0025] Figure 3 This is the infrared spectrum of the attapulgite-based mordenite prepared in Example 1.
[0026] Figure 4 This is the XRD spectrum of the final product of step (2) of comparative example 1.
[0027] Figure 5 This is the N2 adsorption-desorption isotherm diagram of the attapulgite-based mordenite prepared in Example 1.
[0028] Figure 6 This is the pore size distribution diagram of the attapulgite-based mordenite prepared in Example 1. DETAILED DESCRIPTION
[0029] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0030] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.
[0031] Example 1
[0032] Preparation of Cobalt-Nickel / Attapulgite-based Mordenite Catalyst
[0033] The catalyst prepared in this embodiment has an active ingredient cobalt content of 5wt%, a nickel content of 10wt%, and the remaining component is a carrier attapulgite-based mordenite. The preparation method is as follows:
[0034] (1) Weigh 20 g of attapulgite and place it in 120 mL of 6 mol / L hydrochloric acid solution, stir it for 12 h at a temperature of 60 ° C and a stirring speed of 350 r / min, then place it in a polytetrafluoroethylene liner for hydrothermal treatment at 170 ° C for 12 h, then filter and wash it, and dry it at 120 ° C for 12 h to obtain acid-treated attapulgite; weigh 6 g of the acid-treated attapulgite and mix it with tetraethylammonium bromide, sodium hydroxide, sodium aluminate and water in a mass ratio of 1: 0.08: 0.42: 0.1: 40, then hydrothermally crystallize it at 180 ° C for 96 h, then centrifuge the product, wash it with deionized water, and then dry it at 80 ° C for 12 h, finally heat it to 550 ° C at a heating rate of 5 ° C / min in an air atmosphere and calcine it at a constant temperature for 6 h to obtain sodium-type attapulgite-based mordenite.
[0035] (2) The sodium-type attapulgite-based mordenite was added to a 2 mol / L sodium chloride aqueous solution for ion exchange at 90° C. for 4 h. The above operation was repeated three times to obtain the attapulgite-based mordenite.
[0036] (3) Weigh 1 g of attapulgite-based mordenite and 0.2743 g of cobalt nitrate hexahydrate and place them in 200 mL of deionized water. Stir at a stirring rate of 350 r / min at room temperature for 12 h, evaporate the water at 90 °C, and then dry at 80 °C for 12 h. Finally, heat the temperature to 550 °C at a heating rate of 4 °C / min in an air atmosphere and calcine at a constant temperature for 4 h to obtain cobalt / attapulgite-based mordenite.
[0037] (4) 1 g of cobalt / attapulgite-based mordenite and 0.2752 g of nickel nitrate hexahydrate were placed in 200 mL of deionized water, stirred at a stirring rate of 350 r / min at room temperature for 12 h, then the water was evaporated at 90° C., and then dried at 80° C. for 12 h. Finally, the temperature was increased to 600° C. at a heating rate of 4° C. / min in an air atmosphere and calcined at a constant temperature for 6 h to obtain a cobalt-nickel / attapulgite-based mordenite catalyst, numbered C1.
[0038] Example 2
[0039] Preparation of Cobalt-Nickel / Attapulgite-based Mordenite Catalyst
[0040] The catalyst prepared in this embodiment has an active ingredient cobalt content of 5wt%, a nickel content of 5wt%, and the remaining component is a carrier attapulgite-based mordenite. The preparation method is as follows:
[0041] (1) Weigh 6 g of acid-treated attapulgite (the treatment process is the same as that in Example 1), mix it with tetraethylammonium bromide, sodium hydroxide, sodium aluminate and water in a mass ratio of 1:0.08:0.42:0.2:40, and then hydrothermally crystallize it at 160°C for 200 hours. Then, centrifuge the product, wash it with deionized water, and dry it at 70°C for 15 hours. Finally, heat it to 600°C at a heating rate of 4°C / min in an air atmosphere and calcine it at a constant temperature for 4 hours to obtain sodium-type attapulgite-based mordenite.
[0042] (2) The sodium-type attapulgite-based mordenite was added to a 3 mol / L sodium chloride aqueous solution for ion exchange at 90° C. for 4 h. The above operation was repeated three times to obtain the attapulgite-based mordenite.
[0043] (3) Weigh 1 g of attapulgite-based mordenite and 0.2424 cobalt acetylacetonate and dissolve them in 200 mL of anhydrous ethanol. Stir at a stirring rate of 350 r / min at room temperature for 14 h, then evaporate the ethanol at 75 °C, and then dry at 70 °C for 16 h. Finally, heat the temperature to 450 °C in an air atmosphere at a heating rate of 5 °C / min and calcine at a constant temperature for 10 h to obtain cobalt / attapulgite-based mordenite.
[0044] (4) 1 g of cobalt / attapulgite-based mordenite and 0.2432 g of nickel acetylacetonate were placed in 200 mL of anhydrous ethanol, stirred at a stirring rate of 350 r / min at room temperature for 14 h, then the ethanol was evaporated at 75 °C, and then dried at 70 °C for 16 h. Finally, the temperature was increased to 500 °C at a heating rate of 5 °C / min in an air atmosphere and calcined at a constant temperature for 8 h to obtain a cobalt-nickel / attapulgite-based mordenite catalyst, numbered C2.
[0045] Example 3
[0046] Preparation of Cobalt-Nickel / Attapulgite-based Mordenite Catalyst
[0047] The catalyst prepared in this embodiment has an active ingredient cobalt content of 10wt%, a nickel content of 5wt%, and the remaining component is a carrier attapulgite-based mordenite. The preparation method is as follows:
[0048] (1) Weigh 6 g of acid-treated attapulgite (the treatment process is the same as that in Example 1), mix it with tetraethylammonium bromide, sodium hydroxide, sodium aluminate and water in a mass ratio of 1:0.08:0.42:0.3:40, and then hydrothermally crystallize it at 220°C for 92 hours. Then, centrifuge the product, wash it with deionized water, and dry it at 60°C for 18 hours. Finally, heat it to 500°C at a heating rate of 3°C / min in an air atmosphere and calcine it at a constant temperature for 8 hours to obtain sodium-type attapulgite-based mordenite.
[0049] (2) The sodium-type attapulgite-based mordenite was added to a 1 mol / L sodium chloride aqueous solution for ion exchange at 90° C. for 4 h. The above operation was repeated three times to obtain the attapulgite-based mordenite.
[0050] (3) Weigh 1 g of attapulgite-based mordenite and 0.4486 g of cobalt chloride hexahydrate and place them in 200 mL of deionized water. Stir at a stirring rate of 350 r / min at room temperature for 16 h, evaporate the water at 95 °C, and then dry at 60 °C for 20 h. Finally, heat the temperature to 500 °C at a heating rate of 3 °C / min in an air atmosphere and calcine at a constant temperature for 8 h to obtain cobalt / attapulgite-based mordenite.
[0051] (4) 1 g of cobalt / attapulgite-based mordenite and 0.2449 g of nickel chloride hexahydrate were placed in 200 mL of anhydrous ethanol, stirred at a stirring rate of 350 r / min at room temperature for 16 h, then evaporated at 95 °C, and then dried at 60 °C for 20 h. Finally, the temperature was increased to 550 °C at a heating rate of 3 °C / min in an air atmosphere and calcined at a constant temperature for 6 h to obtain a cobalt-nickel / attapulgite-based mordenite catalyst, numbered C3.
[0052] Example 4
[0053] Preparation of Cobalt-Nickel / Attapulgite-based Mordenite Catalyst
[0054] The catalyst prepared in this embodiment has an active ingredient cobalt content of 10wt%, a nickel content of 10wt%, and the remaining component is a carrier attapulgite-based mordenite. The preparation method is as follows:
[0055] (1) Weigh 6 g of acid-treated attapulgite (the treatment process is the same as that in Example 1), mix it with tetraethylammonium bromide, sodium hydroxide, sodium aluminate and water in a mass ratio of 1:0.08:0.42:0.4:40, and then hydrothermally crystallize it at 170°C for 150 hours. Then, centrifuge the product, wash it with deionized water, and dry it at 50°C for 24 hours. Finally, heat it to 450°C in an air atmosphere at a heating rate of 2°C / min and calcine it at a constant temperature for 10 hours to obtain sodium-type attapulgite-based mordenite.
[0056] (2) The sodium-type attapulgite-based mordenite was added to a 4 mol / L sodium chloride aqueous solution for ion exchange at 90° C. for 4 h. The above operation was repeated three times to obtain the attapulgite-based mordenite.
[0057] (3) Weigh 1 g of attapulgite-based mordenite and 0.5962 g of cobalt sulfate heptahydrate and place them in 200 mL of deionized water. Stir at a stirring rate of 350 r / min at room temperature for 18 h, evaporate the water at 90 °C, and then dry at 60 °C for 16 h. Finally, heat the temperature to 600 °C at a heating rate of 2 °C / min in an air atmosphere and calcine at a constant temperature for 4 h to obtain cobalt / attapulgite-based mordenite.
[0058] (4) 1 g of cobalt / attapulgite-based mordenite and 0.5982 g of nickel sulfate heptahydrate were placed in 200 mL of deionized water, stirred at a stirring rate of 350 r / min at room temperature for 18 h, then evaporated to dryness at 90 °C, then dried at 60 °C for 16 h, and finally heated to 600 °C at a heating rate of 2 °C / min in an air atmosphere and calcined at a constant temperature for 4 h to obtain a cobalt-nickel / attapulgite-based mordenite catalyst, numbered C4.
[0059] Example 5
[0060] Preparation of Cobalt-Nickel / Attapulgite-based Mordenite Catalyst
[0061] The catalyst prepared in this embodiment has an active ingredient cobalt content of 15wt%, a nickel content of 15wt%, and the remaining component is a carrier attapulgite-based mordenite. The preparation method is as follows:
[0062] (1) Weigh 6 g of acid-treated attapulgite (the treatment process is the same as that in Example 1), mix it with tetraethylammonium bromide, sodium hydroxide, sodium aluminate and water in a mass ratio of 1:0.08:0.42:0.5:40, and then hydrothermally crystallize it at 200°C for 110 hours. Then, centrifuge the product, wash it with deionized water, and dry it at 60°C for 20 hours. Finally, heat it to 550°C in an air atmosphere at a heating rate of 1°C / min and calcine it at a constant temperature for 6 hours to obtain sodium-type attapulgite-based mordenite.
[0063] (2) The sodium-type attapulgite-based mordenite was added to a 5 mol / L sodium chloride aqueous solution for ion exchange at 90° C. for 4 h. The above operation was repeated three times to obtain the attapulgite-based mordenite.
[0064] (3) Weigh 1 g of attapulgite-based mordenite and 1.333 g of cobalt phosphate octahydrate in 100 mL of methanol, stir at room temperature at a stirring rate of 350 r / min for 20 h, evaporate the methanol at 60 °C, then dry at 50 °C for 24 h, and finally heat the temperature to 500 °C in an air atmosphere at a heating rate of 1 °C / min and calcine at a constant temperature for 6 h to obtain cobalt / attapulgite-based mordenite.
[0065] (4) 1 g of cobalt / attapulgite-based mordenite and 1.331 g of nickel phosphate octahydrate were dissolved in 100 mL of methanol, and stirred at a stirring rate of 350 r / min at room temperature for 20 h. The methanol was evaporated at 60° C., and then dried at 50° C. for 24 h. Finally, the temperature was increased to 450° C. at a heating rate of 1° C. / min in an air atmosphere and calcined at a constant temperature for 10 h to obtain a cobalt-nickel / attapulgite-based mordenite catalyst, numbered C5.
[0066] Comparative Example 1
[0067] Preparation of comparative catalysts
[0068] The preparation process of this comparative example is the same as that of Example 1, except that the crystallization temperature in step (1) is adjusted to 150° C., and the obtained catalyst is numbered D1.
[0069] Comparative Example 2
[0070] Preparation of comparative catalysts
[0071] The preparation process of this comparative example is the same as that of Example 1, except that the crystallization temperature in step (1) is adjusted to 230° C., and the obtained catalyst is numbered D2.
[0072] Comparative Example 3
[0073] Preparation of comparative catalysts
[0074] The preparation process of this comparative example is the same as that of Example 1, except that the amount of sodium hydroxide in step (1) is adjusted to 0.45 times the mass of attapulgite, and the obtained catalyst is numbered D3.
[0075] Comparative Example 4
[0076] Preparation of comparative catalysts
[0077] The preparation process of this comparative example is the same as that of Example 1, except that the constant temperature calcination temperature in step (1) is adjusted to 610° C., and the obtained catalyst is numbered D4.
[0078] Comparative Example 5
[0079] Preparation of comparative catalysts
[0080] The preparation process of this comparative example is the same as that of Example 1, except that step (4) is omitted and the amount of cobalt nitrate hexahydrate in step (3) is adjusted to 0.2599 g, to obtain a catalyst having a cobalt content of 5 wt % and the remaining component being a carrier attapulgite-based mordenite, numbered D5.
[0081] Comparative Example 6
[0082] Preparation of comparative catalysts
[0083] The preparation process of this comparative example is the same as that of Example 1, except that the nickel nitrate hexahydrate in step (4) is replaced by 0.8029 g of zinc nitrate hexahydrate to obtain a catalyst having a cobalt content of 5 wt% and a zinc content of 10 wt% and the remaining component being a carrier attapulgite-based mordenite, numbered D6.
[0084] Comparative Example 7
[0085] Preparation of comparative catalysts
[0086] The preparation process of this comparative example is the same as that of Example 1, except that the carrier in step (3) is replaced by acid-treated attapulgite, and the obtained catalyst is numbered D7.
[0087] Experimental Example 1
[0088] Structural determination of the vector
[0089] The attapulgite-based mordenite prepared in the process of Example 1 was subjected to XRD, SEM and infrared spectrum analysis, and the results were as follows:
[0090] See also Figure 1 , XRD spectrum of attapulgite-based mordenite Figure 2 Characteristic diffraction peaks corresponding to the structure of mordenite were detected at θ=6.5°, 9.8°, 13.5°, 19.7°, 22.4°, 23.3°, 25.8°, 25.7°, 26.4°, 27.7°, 31.1° and 35.9°, proving that the mordenite material was successfully prepared using attapulgite as the silicon source.
[0091] See also Figure 2 From the SEM image of attapulgite-based mordenite, the unique rod-like structure of attapulgite-based mordenite can be observed.
[0092] See also Figure 3 , at 450cm -1 The band at 600 cm-1 can be attributed to the stretching vibration of TO (T = Si / Al) in mordenite; -1The vibration peaks in the region are due to the stretching vibration of the five-membered ring in mordenite; -1 The vibration peak at 1080cm is due to the symmetrical stretching vibration of the tetrahedron in and out of the plane of mordenite; -1 The vibration peaks nearby are attributed to the asymmetric stretching vibrations of the tetrahedrons of mordenite in and out of the plane. The five-membered rings are connected in pairs, that is, two five-membered rings share two tetrahedrons. The five-membered rings in pairs can be connected to another pair of five-membered rings through oxygen bridges, and a four-membered ring is formed at the connection point. If further rings are connected to each other, eight-membered rings and twelve-membered rings can be formed.
[0093] The final product obtained in step (2) of Comparative Example 1 was subjected to XRD analysis, and the results were as follows: Figure 4 As shown, in the hydrothermal crystallization at 150°C, the diffraction peaks appearing in the XRD diagram are inconsistent with those of mordenite, proving that the mordenite structure has not been successfully crystallized under these conditions. In addition, XRD analysis of the final product obtained in step (2) of Comparative Example 2 also revealed that it failed to crystallize into a mordenite structure. However, mordenite structures were detected in Comparative Examples 3 and 4. The inventors have found through a large number of experiments that the crystallization temperature is the most important factor affecting the formation of the mordenite structure. When the crystallization temperature is in the range of 160 to 220°C, the mordenite structure can be obtained within a crystallization time of 92 to 200 hours. However, when the temperature is outside this range, no matter how long the crystallization time is, it cannot be obtained. For the sake of brevity, their XRD diagrams are not attached.
[0094] The pore size and specific surface area of the attapulgite-based mordenite prepared in Examples 1 to 5, Comparative Examples 3 and 4 were measured, and the results are shown in Table 1. The N2 adsorption-desorption isotherm of the attapulgite-based mordenite of Example 1 is shown in Table 1. Figure 5 The pore size distribution diagram is shown in Figure 6 As shown, for the sake of brevity, other embodiments and comparative examples are not repeated here.
[0095] Table 1
[0096]
[0097] It can be seen that the attapulgite-based mordenite prepared in the present invention has a mesoporous structure, while the pore size and specific surface area of Comparative Examples 3 and 4 cannot achieve the effect of the present application after adjusting the amount of sodium hydroxide and the calcination temperature.
[0098] Experimental Example 2
[0099] Performance test of catalyst for catalytic hydrogenation depolymerization of lignin to prepare guaiacol
[0100] Experimental method: Weigh 1g lignin, 0.1-0.5g catalyst, 1-5ml glycerol, 10-50ml deionized water and 0.1-0.5ml formic acid into a high-pressure reactor, fill with 0.1-0.5MPa initial nitrogen pressure, then heat to 270-350℃ within 30min and seal the reaction at a stirring rate of 450r / min for 6-12h. After the reaction is completed, cool with ice water, then filter to remove impurities, and then extract the remaining liquid product with ethyl acetate, then take out the ethyl acetate layer, pass it through a chromatography column containing anhydrous sodium sulfate to remove the incompletely separated water, and finally remove ethyl acetate by rotary evaporation at a temperature of 55℃ and a speed of 65r / min, and quantitatively analyze the rotary evaporation product. Specific reaction conditions and results are shown in Table 2.
[0101] Table 2
[0102]
[0103]
[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A cobalt-nickel / attapulgite-based mordenite catalyst, characterized in that: The invention comprises a carrier and an active component loaded on the carrier, wherein the carrier is attapulgite-based mordenite, the active component is cobalt and nickel, and the attapulgite-based mordenite is prepared by a hydrothermal method using attapulgite as a raw material to obtain the mordenite.
2. The cobalt-nickel / attapulgite-based mordenite catalyst according to claim 1, characterized in that The content of nickel is 5-15wt%, the content of cobalt is 5-15wt%, and the balance is attapulgite-based mordenite.
3. The method for preparing the cobalt-nickel / attapulgite-based mordenite catalyst according to claim 1, characterized in that: The following steps are involved: (1) mixing the acid-treated attapulgite with tetraethylammonium bromide, sodium hydroxide, sodium aluminate and water, and then subjecting the mixture to hydrothermal crystallization. The obtained product is sequentially washed, dried and calcined to obtain sodium-type attapulgite-based mordenite; (2) adding sodium-type attapulgite-based mordenite into a sodium chloride aqueous solution for ion exchange treatment to obtain attapulgite-based mordenite; (3) Cobalt and nickel are loaded on attapulgite-based mordenite to obtain the cobalt-nickel / attapulgite-based mordenite catalyst.
4. The method for preparing the cobalt-nickel / attapulgite-based mordenite catalyst according to claim 3, characterized in that: In step (1), the mass ratio of the acid-treated attapulgite to tetraethylammonium bromide, sodium hydroxide, sodium aluminate and water is 1:0.08:0.42:0.1-0.5:40, and the temperature of the hydrothermal crystallization treatment is 160-220°C, and the time is 92-200h.
5. The method for preparing the cobalt-nickel / attapulgite-based mordenite catalyst according to claim 3, characterized in that: In step (1), the drying temperature is 50-80°C for 12-24 hours; the calcination is carried out in an air atmosphere, and the specific process is to heat the temperature to 450-600°C at a heating rate of 1-5°C / min and calcine for 4-10 hours.
6. The method for preparing the cobalt-nickel / attapulgite-based mordenite catalyst according to claim 3, characterized in that: In step (2), the concentration of the sodium chloride aqueous solution is 1-5 mol / L, the temperature of the ion exchange treatment is 90° C., the time is 4 h, and the number of ion exchange treatments is three times.
7. The method for preparing the cobalt-nickel / attapulgite-based mordenite catalyst according to claim 3, characterized in that: The specific process of step (3) is as follows: adding the attapulgite-based mordenite to the cobalt precursor salt solution, stirring at room temperature for 12 to 24 hours, evaporating the solvent, and then drying at 50 to 80° C. for 12 to 24 hours, and finally calcining at 450 to 600° C. in an air atmosphere at a heating rate of 1 to 5° C. / min for 4 to 10 hours to obtain the cobalt / attapulgite-based mordenite; The cobalt / attapulgite-based mordenite is added to a nickel precursor salt solution, stirred at room temperature for 12 to 24 hours, and then the solvent is evaporated, and then dried at 50 to 80° C. for 12 to 24 hours, and finally calcined at 450 to 600° C. in an air atmosphere at a heating rate of 1 to 5° C. / min for 4 to 10 hours to obtain the cobalt-nickel / attapulgite-based mordenite catalyst.
8. Use of the catalyst according to claim 1 or 2 in catalyzing the depolymerization of lignin to prepare guaiacol under the condition of using water, glycerol and formic acid as reaction solvents and without external hydrogen source.
9. A method for preparing guaiacol by catalytic depolymerization of lignin, characterized in that: The following steps are involved: Glycerol, deionized water and formic acid are mixed in a volume ratio of 1:1 to 10:0.1 to obtain a reaction solvent, and the reaction solvent, lignin and the catalyst as claimed in claim 1 or 2 are put into a reactor for reaction.
10. The method for preparing guaiacol by catalyzing the depolymerization of lignin as claimed in claim 9, characterized in that: The volume mass ratio of the reaction solvent, lignin and catalyst is 11.1-55.5 ml: 1 g: 0.1-0.5 g, and the reaction conditions are temperature 270-350° C., stirring speed 400-800 r / min, and reaction time 6-12 h.
Citation Information
Patent Citations
Method for catalytically converting lignin into aromatic hydrocarbon by using two-step process
CN104387223A
Preparation method of mordenite
CN106745047A
Attapulgite-based ordered microporous zeolite catalyst as well as preparation method and application thereof
CN114308042A
Copper-ruthenium mordenite catalyst for preparing methanol through partial oxidation of coal bed gas, preparation method and application
CN115672384A
Nickel-ruthenium-zirconium / attapulgite-based molecular sieve catalyst and application thereof
CN116237030A